2000
DOI: 10.1142/s021773230000102x
|View full text |Cite
|
Sign up to set email alerts
|

Do the Precise Measurements of the Casimir Force Agree With the Expectations?

Abstract: An upper limit on the Casimir force is found using the dielectric functions of perfect crystalline materials which depend only on well-defined material constants. The force measured with the atomic force microscope is larger than this limit at small separations between bodies and the discrepancy is significant. The simplest modification of the experiment is proposed allowing one to make its results more reliable and answer the question if the discrepancy has any relation with the existence of a new force.The C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(131 citation statements)
references
References 13 publications
(44 reference statements)
5
124
2
Order By: Relevance
“…Lamoreaux 20 was the first who recognized this problem. The reason is very simple: [20][21][22][23] optical properties of deposited films depend on the method of preparation, and can differ substantially from sample to sample.…”
Section: -13mentioning
confidence: 99%
“…Lamoreaux 20 was the first who recognized this problem. The reason is very simple: [20][21][22][23] optical properties of deposited films depend on the method of preparation, and can differ substantially from sample to sample.…”
Section: -13mentioning
confidence: 99%
“…In this case the leading term in the temperature correction is ∼ T 3 [19] and the entropy is safely going to zero as S ∼ T 2 . Two other approaches predict the leading term in the correction ∼ T and finite entropy at T = 0, positive and negative for the approaches [20] and [18], respectively. However, the following analysis revealed that the situation is not as simple.…”
mentioning
confidence: 99%
“…A weak point of this approach is that no known material behaves at a low frequency according to the plasma model. Svetovoy and Lokhanin [20] proposed to use SDM prescription for the n = 0 term in the Lifshitz formula for real metals also. Later it was shown [21] that this prescription follows from a very general dimensional analysis of the classical contribution to the force if one demands continuous transition to the ideal metal case.…”
mentioning
confidence: 99%
“…For example, thin metallic film transparent for visible light gives very significant contribution to the force. 22 On the other hand, a hydrogen-switchable mirror that changes from reflection to transmission in visible light does not give a measurable effect. 23 For practical evaluation of the interaction energy it is convenient to change variables in Eq.…”
Section: Theory a Gold-gold Interaction In The Lifshitz Theorymentioning
confidence: 99%
“…As the dielectric function of Au film we used the data for sample 3 from Ref. 22. The results are presented in Fig.…”
Section: Theory a Gold-gold Interaction In The Lifshitz Theorymentioning
confidence: 99%